2023
DOI: 10.1051/sicotj/2022050
|View full text |Cite
|
Sign up to set email alerts
|

No dislocation and low complication rate for a modern dual mobility cup with pre-impacted femoral head in primary hip replacement: A consecutive series of 175 hips at minimum 5-year follow-up

Abstract: Introduction: Despite its excellent results in preventing dislocation, the dual mobility cup (DMC) is still struggling to be adopted by some teams due to premature wear and loosening reported on first-generation implants. Therefore, this study aimed to assess the mid-term survivorship of a modern DMC with a pre-impacted head and the radio-clinical results at a minimum follow-up of 5 years. Methods: This was a retrospective single-centre study performed on patients who had a primary total hip replacement for os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Total hip arthroplasty (THA) stands as a successful procedure for hip osteoarthritis and over time, technological advancements, including different types of cementless fixation and design philosophies, have expanded the implant options, indications, and age-group target [1][2][3][4][5]. The Corail stem Ò (DePuy Synthes) is a non-cemented, fully hydroxyapatite-coated femoral stem made of forged titanium alloy for hip reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Total hip arthroplasty (THA) stands as a successful procedure for hip osteoarthritis and over time, technological advancements, including different types of cementless fixation and design philosophies, have expanded the implant options, indications, and age-group target [1][2][3][4][5]. The Corail stem Ò (DePuy Synthes) is a non-cemented, fully hydroxyapatite-coated femoral stem made of forged titanium alloy for hip reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 63 articles included, 11 reported outcomes for two different approaches in the same study [ 10 , 33 , 40 , 43 , 49 , 50 , 52 , 69 , 79 , 84 ], and one study reported three approaches [ 74 ], resulting in 75 total study arms. Eight studies reported the DAA, five reported the ALA, six reported the DLA, and 56 studies reported the PLA (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dual mobility cups were used for patients older than 65 and those with a high risk of dislocation (e.g. epilepsy, Parkinson’s disease, substance abuse) [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%